2020
DOI: 10.1155/2020/1019238
|View full text |Cite
|
Sign up to set email alerts
|

Possible Factors Influencing the Seroprevalence of Dengue among Residents of the Forest Fringe Areas of Peninsular Malaysia

Abstract: Dengue is an endemic mosquito-borne viral disease prevalent in many urban areas of the tropic, especially the Southeast Asia. Its presence among the indigenous population of Peninsular Malaysia (Orang Asli), however, has not been well described. The present study was performed to investigate the seroprevalence of dengue among the Orang Asli (OA) residing at the forest fringe areas of Peninsular Malaysia and determine the factors that could affect the transmission of dengue among the OA. Eight OA communities co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…There were no studies examining YFV. Included studies consisted of 2 cohort studies,16 17 4 case–control studies,18–21 27 cross-sectional studies,22–48 1 nested cross-sectional study within a cohort,49 1 combined cross-sectional and cohort study50 and 1 longitudinal serosurvey 51. Studies were conducted in 23 countries: 4 in low-income countries (Burkina Faso,42 Laos35 and Sudan26 43), 14 in lower-middle-income countries (Ecuador,41 India,19 Jordan,33 37 Kenya,17 36 Nicaragua,16 50 Nigeria,27 31 40 Pakistan,39 Sri Lanka18 and Vietnam34), 13 in upper-middle income (Brazil,23 30 45–47 China,20 24 38 Colombia,49 51 Malaysia,25 Paraguay44 and Thailand29) and 5 in high-income countries/territories (Mayotte (France),28 French Guiana,21 Saudi Arabia,22 Sweden32 and USA48) according to the Development Assistance Committee List of Official Development Assistance Recipients (figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no studies examining YFV. Included studies consisted of 2 cohort studies,16 17 4 case–control studies,18–21 27 cross-sectional studies,22–48 1 nested cross-sectional study within a cohort,49 1 combined cross-sectional and cohort study50 and 1 longitudinal serosurvey 51. Studies were conducted in 23 countries: 4 in low-income countries (Burkina Faso,42 Laos35 and Sudan26 43), 14 in lower-middle-income countries (Ecuador,41 India,19 Jordan,33 37 Kenya,17 36 Nicaragua,16 50 Nigeria,27 31 40 Pakistan,39 Sri Lanka18 and Vietnam34), 13 in upper-middle income (Brazil,23 30 45–47 China,20 24 38 Colombia,49 51 Malaysia,25 Paraguay44 and Thailand29) and 5 in high-income countries/territories (Mayotte (France),28 French Guiana,21 Saudi Arabia,22 Sweden32 and USA48) according to the Development Assistance Committee List of Official Development Assistance Recipients (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The association between education and arboviral infection was analysed in 1 cross-sectional study nested in a cohort, 2 case–control and 22 cross-sectional studies, spanning 18 countries and 6 arboviruses (CHIKV, DENV, JEV, RVFV, SINV and WNV). In these studies, education was classified in distinct ways depending on context, and included level of education,19 24 26 27 29 31–34 36 38–41 43 44 49 schooling age,23 parental education,20 the attainment of any formal education,25 37 42 length of education in years28 and illiteracy 30 45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was also a study on the potential of urban forests to be a form of preventive medicine via forest therapy [28,29]. Additionally, as mentioned previously, there was also a nationwide study on the role of urban forests in the spread of Dengue [15]. The study found that there was a positive correlation between the occurrence of dengue with the presence of a lake.…”
Section: Distribution Of Articles Based On Research Themesmentioning
confidence: 89%
“…There were four articles that conducted their studies in multiple locations [11][12][13][14]. There was also a study conducted throughout Peninsular Malaysia, whereby the research was on the prevalence of dengue among residents residing on the fringe areas of urban forests [15].…”
Section: Distribution Of Articles Based On Locationmentioning
confidence: 99%